Improved Campus Security Tracking Technology With NFC System - Aditya Maulana; Tarigan, Adi Sastra P.; Hamdani, (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
Smart Card is the main support in the gate system. This study aims to apply smart cards to smart gates among the academic community as users. This system uses a MIFARE type Near Field Communication (NFC) smart card as an identity for identification and authentication. The read/write process is configured where data blocks can be read using the Arduino integrated hardware. Information security on NFC tags is carried out using Caesar Chipper encryption and the rotary letter method. The time needed to read information from the database to the NFC tag without a barrier is the fastest time of 1.49 deTechnology and the longest 2.26 deTechnology with an average processing time of 1.84 deTechnology, while for testing using the fastest time barrier it is obtained 1, 53 deTechnology and the longest time is 2.21 deTechnology with an average processing time of 1.83 deTechnology. This shows that the time used in the process of writing information is efficient and is not affected by obstacles.